Moral and spiritual leadership in an age of plural moralities - Alma, Hans 1962-; Avest, Ina ter (Studies in world Christianity and interreligious relations, 2019)
In crisis situations, such as terror attacks or societal tensions caused by migration, people tend to look for explicit moral and spiritual leadership and are often inclined to vote for so-called 'strong leaders'. Is there a way to resist the temptation of the simplistic solutions that these 'strong leader' offer, and instead encourage constructive engagement with the complex demands of our times? This volume utilises relational and dialogical perspectives to examine and address many of the issues surrounding the moral and spiritual guidance articulated in globalizing Western societies. The essays in this collection focus on the concept of plural moralities, understood as divergent visions on what is a 'good life', both in an ethical, aesthetical, existential, and spiritual sense. They explore the political-cultural context and consequences of plural moralities as well as discussing challenges, possibilities, risks, and dangers from the perspective of two promising relational theories: social constructionism and dialogical self theory. The overarching argument is that it is possible to constructively put in nuanced moral and spiritual guidance into complex, plural societies. By choosing a clear theoretical focus on relational approaches to societal challenges, this interdisciplinary book provides both a broad scope and a coherent argument. It will be of great interest to scholars of social and political psychology, leadership and organization, religious studies, and pedagogy